A expressividade no choro: um estudo a partir de perspectivas da Etnomusicologia e da Fenomenologia - Paulo Vinícius Amado (2014)
The Choro (brazilian instrumental music) is characterized, according to scholars and enthusiast, by specific "gestures" of interpretation and musical expressiveness. The issue of musical expressiveness, therein, is the subject of the most discussed by thinkers and musicians from different eras, and the consensus on this topic has not been reached. About the Choro's specific musical expressiveness, the reality is no different. The objective of this work, thus, is try understand some of the characteristics in the context and Choro's musical expression and contribute, in some order, for your comprehension. In this way, the research revolves around an ethnographic-phenomenological account from field work conducted in the Belo Horizonte's Rodas de Choro. After that, the task is the development a closer relationship between epistemological notes arising from the complex formulation of the theoretical frameworks particularly the Ethnomusicology and Phenomenology and oriented literature's review; and effective realization a hearing-observation-participation in musical events, specifically "Rodas de Choro" in the Minas Gerais capital.